LINE-1 hypomethylation is not a common event in preneoplastic stages of gastric carcinogenesis - Juozas Kupcinskas (Nature Portfolio, 2017)
Abstract LINE-1 hypomethylation is widely accepted as marker for global genomic DNA hypomethylation, which is a frequent event in cancer. The aim of the study was to evaluate LINE-1 methylation status at different stages of gastric carcinogenesis and evaluate its prognostic potential in clinical settings. LINE-1 methylation was analyzed in 267 tissue samples by bisulfite pyrosequencing including primary colorectal cancer tissues (T-CRC) with corresponding adjacent colon mucosa (N-CRC), gastric cancer tissues (T-GC) with corresponding gastric mucosa (N-GC), normal gastric tissues (N), chronic non-atrophic and atrophic gastritis (CG). LINE-1 methylation level was lower in both T-GC and T-CRC when compared to paired adjacent tissues. No difference was observed for LINE-1 methylation status between patients with normal gastric mucosa, CG and N-GC. LINE-1 methylation in T-GC but not N-GC tended to correlate with age. Subgroup stratification analysis did not reveal significant differences in LINE-1 methylation status according to tumor stage, anatomical location, histological subtype, differentiation grade. We observed similar overall survival data between patients with high or low LINE-1 levels. In summary, LINE-1 hypomethylation is a characteristic feature in GC but not very common in early preneoplastic stages of gastric carcinogenesis. Prognostic role of LINE-1 hypomethylation in GC patients could not be confirmed in this cohort.